'n Pastoraal-narratiewe groepsontwikkelingsmodel vir vrywilligers van die Kankervereniging - J. Steyn; J-A. van den Berg (Acta Theologica)
The caregivers of the Cancer Association of South Africa (CANSA), Bloemfontein expressed their need to develop lay-counselling skills in order to assist the patient to cope with life during illness. Ten out of twelve caregivers indicated that they had a nursing background whilst two previously attended courses in lay-counselling. In order to offer assistance to a person acquiring coping skills, a caregiver should have a clear perspective on his/her own life story. Guiding the caregivers in achieving lay-counselling skills in caring for the sick, the group method was chosen. The first aim was to facilitate growth in understanding that every person was born in the “Narrative of God” (Ps. 139) and baptised in the name of God, Jesus Christ and the Holy Spirit (Matthew 28:19). Each person therefore has value in Jesus Christ. A second aim was to facilitate the developing of lay-counselling skills by means of sharing narratives. Group dynamics underpinned the developing of these skills by interaction. The achievement resulted in an enriching spiritual capacity of acknowledging the work of the Holy Spirit in the life and work of the caregivers.